Colonization With Extensively Drug-Resistant Acinetobacter baumannii and Prognosis in Critically Ill Patients: An Observational Cohort Study - Zheng, Yue; Xu, Nana; Pang, Jiaojiao; Han, Hui; Yang, Hongna; Qin, Weidong; Zhang, Hui; Li, Wei; Wang, Hao; Chen, Yuguo (Frontiers in Medicine, 2021)
Background: Acinetobacter baumannii is one of the most frequently isolated opportunistic pathogens in intensive care units (ICUs). Extensively drug-resistant A. baumannii (XDR-AB) strains lack susceptibility to almost all antibiotics and pose a heavy burden on healthcare institutions. In this study, we evaluated the impact of XDR-AB colonization on both the short-term and long-term survival of critically ill patients. Methods: We prospectively enrolled patients from two adult ICUs in Qilu Hospital of Shandong University from March 2018 through December 2018. Using nasopharyngeal and perirectal swabs, we evaluated the presence of XDR-AB colonization. Participants were followed up for 6 months. The primary endpoints were 28-day and 6-month mortality after ICU admission. The overall survival rate was estimated by the Kaplan-Meier method. We identified risk factors associated with 28-day and 6-month mortality using the logistic regression model and a time-dependent Cox regression model, respectively. Results: Out of 431 patients, 77 were colonized with XDR-AB. Based on the Kaplan-Meier curve results, the overall survival before 28 days did not differ by colonization status; however, a significantly lower overall survival rate was obtained at 6 months in colonized patients. Univariate and multivariate analysis results confirmed that XDR-AB colonization was not associated with 28-day mortality, but was an independent risk factor of lower overall survival at 6 months (HR = 1.749, 95% CI = 1.174–2.608). Conclusions: XDR-AB colonization has no effect on short-term overall survival, but is associated with lower long-term overall survival in critically ill patients.